2014
DOI: 10.1038/ncomms6544
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic dynein transports cargos via load-sharing between the heads

Abstract: Cytoplasmic dynein is a motor protein that walks along microtubules (MTs) and performs mechanical work to power a variety of cellular processes. It remains unclear how a dynein dimer is able to transport cargos against load without coordinating the stepping cycles of its two heads. Here, by using a DNA-tethered optical trapping geometry, we find that the force-generating step of a head occurs in the MT-bound state, while the ‘primed’ unbound state is highly diffusional and only weakly biased to step towards th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 36 publications
8
72
0
Order By: Relevance
“…4A), such that the velocity changes slowly at small forces, as shown in experiments (25). In contrast, for other motor proteins with a strong χ vel (F), such as myosins and dyneins, the velocity sharply diminishes at low external loads (26,27), following the lower curve (red in Fig. 4A).…”
Section: Geometric Constraints Cause Uneven Force Partitioning Betweementioning
confidence: 94%
See 1 more Smart Citation
“…4A), such that the velocity changes slowly at small forces, as shown in experiments (25). In contrast, for other motor proteins with a strong χ vel (F), such as myosins and dyneins, the velocity sharply diminishes at low external loads (26,27), following the lower curve (red in Fig. 4A).…”
Section: Geometric Constraints Cause Uneven Force Partitioning Betweementioning
confidence: 94%
“…Previous single-molecule analyses have shown that the kinesin motor velocity changes sluggishly at low loads [i.e., χ vel (F) is low below the single-kinesin stalling force] (25). In contrast, the velocities of single myosin and dynein motors decrease much more rapidly at low loads, yielding a stronger χ vel (F) in the same loading regime (26,27). Herein, we pinpointed the molecular origin of the weak χ vel (F) for kinesins by analyzing the impact of loading forces on the transition rates in the chemomechanical cycle.…”
mentioning
confidence: 88%
“…At 8.3 nm, 16.6 nm, and 24.9 nm of separation, d t , between the MT-binding sites, the deflection sizes of the rings, d r , along the MTs are calculated to be 0.18 nm, 0.37 nm, and 0.55 nm, respectively, d t = d c + 2·d r = F c ·(1/k c + 2·C s ), and corresponding step sizes measured at the ring, s r = d c , are 7.9 nm, 15.9 nm, and 23.8 nm, thereby broadening the distribution of measured step sizes. Intramolecular forces at the three values of d t are 0.2 pN, 0.4 pN, and 0.6 pN, which are well within the 3-to 5-pN forcegenerating capability of the motor (43,46,53,54).…”
Section: Discussionmentioning
confidence: 61%
“…Ring rotations were also measured in the context of a heterodimer with one inactive or "dead" head ( Fig. 4 A and B), because it has been shown that a dynein construct having only a single active head is still able to move processively as long as the second head retains the ability bind to the MT (46). We used a heterodimeric construct in which the active head was doubly biotinylated and labeled with a QR, whereas the other unlabeled head contained a P-loop (Walker A) K-to-A mutation in AAA1, which renders it unable to bind or hydrolyze ATP (47).…”
Section: Resultsmentioning
confidence: 99%
“…It has two ~550 kD heavy chains with multiple ATP binding sites, three to four intermediate chains of ~74 kD, four light intermediate chains of ~55 kD, and several light chains of 8-22 kD (Nishikawa et al, 2014;Belyy et al, 2014;Bhabha et al, 2016). Cytoplasmic dynein plays essential roles in many cellular processes, as it can hydrolysis ATP to generate force to move on and towards the minus end of the microtubule (Karki and Holzbaur, 1999;Roberts et al, 2013).…”
Section: Introductionmentioning
confidence: 99%